Management and Outcomes of ANCA-Associated Vasculitis at a Tertiary Healthcare Facility. (11th February 2022) - Moollan, Nabeehah; Ahmed, Adeel Rafi; Denton, Mark
Abstract : Purpose of the Study . Antineutrophil cytoplasmic antibody- (ANCA-) associated vasculitis (AAV) is a rare multisystem autoimmune condition with an incidence of 0.4–24 per 1 million person- years. The severity of renal involvement predicts prognosis. Limited data are available on its management and outcomes; thus, we aim to assess this at our tertiary-care renal facility. Study Design. Retrospective data were collected using our national renal electronic database (eMED) to identify AAV patients over a period of 6 years. Outcomes included progression to end-stage renal disease (ESRD) or death, chronic kidney disease (CKD), and preservation of renal function. Results . Thirty-six patients were included in the final study. Cyclophosphamide was used in 24 patients (66.7%) and, comparatively, rituximab in 7 patients (19.4%) for induction. Seven patients (19.4%) had a documented relapse, and six patients (85.7%) had rituximab as induction therapy for relapse. The majority of patients were on azathioprine (61.1%, 57.1% relapse population) as maintenance therapy. Progression to ESRD occurred in 11 (30.6%), death in 4 (11.1%), established CKD in 15 (41.7%), and preservation of renal function in 6 (16.7%) patients by the end of the follow-up period. Conclusions . While cyclophosphamide remains the choice of induction immunosuppression therapy, we favour rituximab as an induction agent in the relapse of AAV. Despite aggressive immunosuppression therapy, the incidence of ESRD and death remains high in these patients.